2001
DOI: 10.12968/bjon.2001.10.16.9371
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac rehabilitation: the needs of South Asian cardiac patients

Abstract: There is an indication that South Asian people in the UK experience greater delays than white British populations in obtaining appropriate treatment and intervention despite experiencing higher levels of coronary heart disease (Chaturvedi et al, 1997). Evidence suggests that access to and uptake of UK cardiac rehabilitation services is disproportionately low in South Asian populations (NHS Centre for Reviews and Dissemination, 1998). This article examines the results of an audit of cardiac rehabilitation among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…A language barrier has been reported as an obstacle to information provision for South Asian cardiac patients in other studies 11,12 . It has been suggested that cardiac patients of South Asian origin might be disadvantaged in terms of knowledge and awareness about their condition; first by not always having the choice to access trained interpreters whilst in hospital and second, by the reliance on written information that incorrectly assumes that the whole population is able to read 27 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A language barrier has been reported as an obstacle to information provision for South Asian cardiac patients in other studies 11,12 . It has been suggested that cardiac patients of South Asian origin might be disadvantaged in terms of knowledge and awareness about their condition; first by not always having the choice to access trained interpreters whilst in hospital and second, by the reliance on written information that incorrectly assumes that the whole population is able to read 27 .…”
Section: Discussionmentioning
confidence: 99%
“…The key to progression in this arena is for health care professionals to know when ethnicity makes a difference and mediates a person's relationship with service support and when it does not. One example of this is the shortage of appropriate translation and interpreting facilities in the context of healthcare provision that has been identified as a problem 11,12,27. .…”
Section: Conclusion and Implications For Practicementioning
confidence: 99%
“…50 An audit in the UK found that South-Asian patients were less likely to have attended CR, largely due to communication difficulties. 60 A systematic review of determinants of referral to cardiac rehabilitation in 30,333 participants in 10 observational studies from the USA, Australia and Canada found that speaking English was strongly associated with referral to CR [relative risk (RR) 9.56, 95% confidence interval (CI) 2.18 to 41.93]. 61 However, these studies had a very low overall rate of participants from an ethnic minority group.…”
Section: Uptake and Adherence In Under-represented Groupsmentioning
confidence: 99%
“…Tod and colleagues also identified ill-health as a cause of non-adherence to CR in patients of South Asian ethnicity. 60 Some patients had adapted the programme to suit their own needs because of co-morbidity or personal circumstances and were exercising at a low level not likely to reproduce the benefits found in randomised trials. Women, in particular, were more likely to describe the resumption of domestic tasks as a replacement for formal exercise.…”
Section: Non-adherers To Cardiac Rehabilitationmentioning
confidence: 99%
“…39 No similar surveys have been published in the UK, but a retrospective hospital audit found low attendance at cardiac rehabilitation among patients of South Asian origin. 60 This was attributed to poor access and inadequate use of interpreting services by patients and staff, and lack of translated written information.…”
Section: Under-representation In Cardiac Rehabilitationmentioning
confidence: 99%